Cold hibernated elastic memory foams for endovascular interventions - Metcalfe, Annick; Desfaits, Anne-Cécile; Salazkin, Igor; Yahia, L’Hocine; Sokolowski, Witold M; Raymond, Jean (Biomaterials, 2003)
Cold hibernated elastic memory (CHEM) polyurethane-based foam is a new shape memory polymeric self-deployable structure. Standard cytotoxicity and mutagenicity tests were conducted on CHEM in vitro, to ensure biocompatibility before studying potential medical applications. In vivo, lateral wall aneurysms were constructed on both carotid arteries of eight dogs. Aneurysms were occluded per-operatively with CHEM blocks. In two dogs, CHEM embolization was compared with gelatin sponge fragment embolization. Internal maxillary arteries (Imax) were also occluded with CHEM using a 6F transcatheter technique. Angiography and pathology were used to study the evolution of aneurysms and Imax at 3 and 12 weeks. Imax embolized with CHEM foam remained occluded at 3 weeks. Most aneurysms embolized with CHEM showed a small residual crescent of opacification at initial angiography, but angiographic scores were significantly better at 3 weeks. Thick neointima formation over the CHEM at the neck of aneurysms was demonstrated at pathology. The foamy nature of CHEM favours the ingrowth of cells involved in neointima formation. New devices for endovascular interventions could be designed using CHEM's unique physical properties.